Effect of Mineral Supplementation and Introduction of Setaria sphacelata Grass and Gliricidia sepium Legume on Productivity of Kacang Goat at Serang River Basin Upland Area, Central Java, ndonesia - Widiyanto; Pangestu, E.; Surahmanto; Yunianto, V.D.; Tampoebolon, B.I.M.; Prasetiyono, B.W.H.E. (Pakistan Journal of Nutrition, 2015)
This experiment was conducted at the upland area of Serang river basin, to study the influence of Setaria sphacelata grass and Gliricidia sepium legume forages feeding in combination with mineral supplementation on nutritional status and performance of Kacang goat. Twenty four male Kacang goats (14.01±0.6 kg) were used as experimental materials. First factor were: F0 (100% conventional forage), F1 (70% conventional forage + 30% Setaria), F2 (40% conventional forage + 30% Setaria + 30% Gliricidia), F3 (20% conventional forage + 30% Setaria + 50% Gliricidia). The second factor, namely: S0 (without supplementation) and S1 (mineral supplementation). The data were analyzed by analysis of variance with 4 × 2 × 3 factorial arrangement in randomized completely block design. The dry matter (DM) consumption in F2 and F3 were higher (p<0.05) than that in F0 and F1 treatment groups (301.1 and 328.9 vs 219 and 241.7 g/head/day, respectively). The in vivo dry matter digestibility (IVoDMD) in F2 and F3 were higher (p<0.05) than that in F1, but non significantly different from F0. The average daily gain (ADG) of goats in F0, F2 and F3 were higher (p<0.05) than F1 treatment group (namely: 35.72, 35.95 and 37.42 vs 34.55 g/head/day). Feeding 30% Setaria sphacelata grass and 50% Gliricidia sepium legume increased ADG of Kacang goat. Mineral supplementation improved the Ca and P status and Kacang goat ADG.